Comprehensive Bibliometric Analysis and Systematic Review of Two Decades of Food Vendors Study: Deciphering the Dynamics of Food Vendor Research - Manoharan, Ajay Adithya; Rangaswamy, Geetha (International Review of Management and Marketing, 2024)
This study examines food vendor research over a two-decade period (2005-2023), using both bibliometric and systematic review approaches. Using data from the Scopus database with 421 articles, the study shows a significant increase in research production, with a focus on food security, consumer behavior, and the influence of COVID-19. The bibliometric analysis reveals major study issues, such as food safety, sustainability, and the informal sector, while a systematic examination of the top 20 most-cited publications provides additional insight into the research landscape. This review emphasizes the need of include time in food accessibility studies, the need for a more nuanced understanding of food deserts, and the increased interest in organic vegetable marketing and insect eating. Also this is the first article which completely drafted in the perspective of food vendors. The study concludes by identifying limitations and suggesting future research directions, emphasizing the importance of an interdisciplinary approach, incorporating qualitative methods, focusing on specific regions, investigating the impact of the internet, and delving deeper into purchasing habits, sustainability, and socioeconomic impacts. This thorough analysis lays the groundwork for future research, encouraging the creation of more fair, sustainable, and resilient food systems.